2019
DOI: 10.1021/acs.jpca.9b00041
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Infrared Spectra of [M(CO2)7]+ (M = V, Cr, and Mn) Complexes

Abstract: Gas-phase infrared photodissociation spectra of [V­(CO2) n ]+ complexes revealed three new vibrational bands at 1140, 1800, and 3008 cm–1 at n = 7, the features of which are retained in the larger clusters (Ricks, A. M.; Brathwaite, A. D.; Duncan, M. A. J. Phys. Chem. A 2013, 117, 11490–11498). However, structural assignment of this intriguing feature remains open. Herein, quantum chemical calculations on [V­(CO2)7]+ were carried out to identify the structure of the low-lying isomers and to assign the observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…In contrast, the CO 2 molecule was only weakly bound to the metal cations, exclusively in an end-on configuration via electrostatic charge-quadrupole interaction, resulting in a linear M + OCO structure. The antisymmetric CO 2 stretching vibrations in these cationic complexes are generally blue-shifted with respect to the free CO 2 molecule. It was found that these blue-shifted vibrations vary only slightly from one system to another due to electrostatic interaction. Here we report the generation of the cationic metal complex BeOCO + , which exhibits an antisymmetric CO 2 stretching mode at 2418.9 cm –1 in solid neon, blue-shifted by 71 cm –1 with respect to free CO 2 . The observed value is the highest antisymmetric CO 2 stretching frequency ever reported for a carbon dioxide complex. …”
Section: Introductionmentioning
confidence: 83%
“…In contrast, the CO 2 molecule was only weakly bound to the metal cations, exclusively in an end-on configuration via electrostatic charge-quadrupole interaction, resulting in a linear M + OCO structure. The antisymmetric CO 2 stretching vibrations in these cationic complexes are generally blue-shifted with respect to the free CO 2 molecule. It was found that these blue-shifted vibrations vary only slightly from one system to another due to electrostatic interaction. Here we report the generation of the cationic metal complex BeOCO + , which exhibits an antisymmetric CO 2 stretching mode at 2418.9 cm –1 in solid neon, blue-shifted by 71 cm –1 with respect to free CO 2 . The observed value is the highest antisymmetric CO 2 stretching frequency ever reported for a carbon dioxide complex. …”
Section: Introductionmentioning
confidence: 83%
“…Only larger Co n À (n 4 8) clusters bind CO 2 at all 5 whilst CO 2 binds molecularly to small Pt n À clusters (n o 5) but dissociatively on larger ones. 6 Metal cations necessarily donate electron density less effectively than anions and M + (CO 2 ) binding is usually M(Z 1 -OCO), 4,[23][24][25][26][27][28] dictated by the dominant charge-quadrupole interactions and s-donation. The typical spectroscopic signature of such binding is a weak blue shift in the CO 2 asymmetric stretch around 2349 cm À1 .…”
Section: Introductionmentioning
confidence: 99%
“…27 Metal cationligand electron transfer reaction in forming an oxalate-type C 2 O 4 anion species was proposed in the V(CO 2 ) n + n Z 7 clusters, 28 which was later reassigned to a charge transfer complex involving a bidentate Z 2 -C, O coordinated CO 2 À ligand. 33 Solvation-induced intracluster insertion reaction producing the oxocarbonyl species has also been reported in the larger [M(CO 2 ) n ] + complexes with M = Ti, Ni, Si and n Z5. [24][25][26] Recent investigation on the end-on Z 1 -O coordinated [BeOCO] + complex in solid neon matrix indicates that the bonding between the metal cation and CO 2 exhibits significant covalent character due to the interference of the wave function.…”
Section: Introductionmentioning
confidence: 83%
“…15,20 The CO 2 ligand is bound to the metal center exclusively in an end-on Z 1 -O fashion in the cationic complexes. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The binding between the metal cation and carbon dioxide is largely an electrostatic interaction, resulting in a blue-shifted antisymmetric CO 2 stretching vibration with respect to the free CO 2 molecule. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Solvation-induced metal cationcarbon dioxide electron transfer with the formation of a bent CO 2 À moiety was reported on the Mg(H 2 O) n (CO 2 ) + complexes with n Z 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation